Performance assessment of the proton exchange membrane fuel cell - chemical heat pump hybrid system. (July 2018) - Açıkkalp, Emin; Caliskan, Hakan
Abstract: In this paper, a hybrid system that consists of proton exchange membrane fuel cell and chemical heat pump is investigated. In terms of power outputs, the maximum points and higher power outputs are obtained at the current densities between 1-2 A/cm 2 . In contrast, higher energy efficiencies are provided at low current densities. According to the results, the higher power output can be provided at higher current densities. However, at these current densities hybrid system has smaller energy efficiency. For better efficient and environmental utilization of the hybrid system, it should be used under condition of i η < i < i P ( i η and iP are current densities at the maximum efficiency and maximum power, respectively). However, its current density should be closer to current density at maximum power.